Kembangan Dam Safety Risk Index Sragen Regency - Arbal Fadli; Ignatius Sriyana; Sri Sangkawati (International Journal of Science and Society, 2023)
In dam management, in addition to the safety factors of the structure and condition of the dam and the emergency action plan that needs to be prepared, other elements that need to be considered are the operation, maintenance, monitoring and observation activities of the dam. In extreme circumstances, mistakes in dam operations can be fatal. The dam can fail and cause a massive flood that can damage facilities and infrastructure, and even loss of life downstream of the dam. Risk assessment is a way to identify risks that may occur under various conditions, so that the necessary follow-up can be done if the risk is unacceptable. In this study, a risk assessment was conducted to obtain a safety value for the Kembangan Dam located in Karangmalang District, Sragen Regency, Center Java Province. The method used in this research is to use the risk index method. The risk index method assessment parameters are obtained from the initial importance factor of the dam (I dam), the calculation of the total risk index of the dam (IR tot), and the safety value of the dam (N aman). The results showed that the Kembangan dam had an initial importance factor (I dam) of 356.25, a total risk index (IR tot) of 66.618, and a dam safety value (N aman) of 81.3. Thus, it can be concluded that the safety level of the Kembangan dam is included in the Kembangan clause.